Optymalna niejednorodność plastyczna skręcanego pręta jako zagadnienie numeryczne - MIODUCHOWSKI, Andrzej (Engineering Transactions, 1971)
Optimal plastic inhomogeneity of a twisted rod as a numerical problem Twisted prismatic rods of a diagonal continuous plastic inhomogeneity are considered. On the basis of an incomplete gradient method and a method of modified local variations, an attempt is made to find, by numerical means, an optimal dissolution of that inhomogeneity – that is, such a dissolution as gives a maximal boundary bearing.The example considered was a prismatic rod of square diameter, for several cases of different limitations imposed on the plastic inhomogeneity function. Practical engineering results are given for constructional elements of this type.